Mental health of primary health care physicians and nurses following prolonged infection control rules: a national survey in China - Li, Crystal Jingru; Zheng, Yanling; Gan, Yong; Du, Zhaohui; Cai, Xuemin; Li, Yongjin; Wang, Wei; Jiang, Tianwu; Zhang, Qingyu; Niu, Lei; Tao, Tiffany Junchen; Hou, Wai Kai (Frontiers in Public Health, 2024)
Introduction: This study examined the prevalence and correlates of probable mental health disorders, including psychological distress, somatization, depression, anxiety, phobic anxiety (PHO), obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), and insomnia among Chinese primary health care (PHC) physicians and nurses amid the postpandemic period in 2022.Method: Region-stratified sampling was conducted to recruit a national sample of 4,246 respondents from 31 July 2022 to 12 August 2022. 692 primary healthcare institutions were identified in 30 provincial-level administrative regions of China. An online questionnaire was used for measurement, including Symptoms Checklist-90-Revised (SCL-90-R), PTSD Checklist for DSM-5 (PCL-5), and Insomnia Severity Index (ISI). Demographic and workrelated variables were also assessed. Bivariate analysis and multiple logistic regression were conducted to identify significant correlates of probable mental health disorders.Results: A total of 4,246 valid questionnaires were identified. Results showed that relative to prevalence of probable mental health disorders among health care workers at the early stage of the pandemic in China, there was an overall decreased prevalence except for somatization, PHO, and OCD among the current PHC physicians and nurses. Multiple logistic regressions showed that significant risk factors of all the current probable mental health disorders were female gender, overtime work, multimorbidity, history of psychiatric disorders, quarantine experience, and never asking anyone for help.Attention should be given to preexisting psychiatric and multimorbid conditions, work-related stressors, and social support. Regular assessment and psychological interventions could enhance the mental health of PHC professionals.